THE SCIENCE OF GETTING RICH - Wattles, Wallace D., 1860-1911, author 313758; Fine, Rebecca, author 651747 (Singapore : Success Shop, 2005)
As featured in the bestselling book The Secret, here is the landmark guide to wealth creation republished with the classic essay “How to Get What You Want.” Wallace D. Wattles spent a lifetime considering the laws of success as he found them in the work of the world’s great philosophers. He then turned his life effort into this simple, slender book – a volume that he vowed could replace libraries of philosophy, spirituality, and self-help for the purpose of attaining one definite goal: a life of prosperity.Wattles describes a definite science of wealth attraction, built on the foundation of one commanding idea: “There is a thinking stuff from which all things are made…A thought, in this substance, produces the thing that is imaged by the thought.”In his seventeen short, straight-to-the-point chapters, Wattles shows how to use this idea, how to overcome barriers to its application, and how work with very direct methods that awaken it in your life. He further explains how creation and not competition is the hidden key to wealth attraction, and how your power to get rich uplifts everyone around you. The Science of Getting Rich concludes with Wattle’s rare essay “How to Get Want You Want” – a brilliant refresher of his laws of wealth creation.